The significance of a calling, whether secular or spiritual - Baack, Kyle T (Kansas State University, 2013)
Hall and Chandler argued that one of the deepest forms of satisfaction or psychological success can occur when the person experiences work as more than a job or career – when it is a calling (2005, p. 160). They defined calling as work that a person perceives as his purpose in life. Adams (2012) said “there has been a recent awareness of the need to find ways to incorporate meaning into people’s work (p. 66).” Steger defined meaning as “the extent to which people comprehend, make sense of, or see significance in their lives, accompanied by the degree to which they perceive themselves to have a purpose, mission, or over-arching aim in life” (Steger, 2009, p. 680). Historically, an individual received an external calling from God but today another type of calling is being discussed: that of an internal calling. The Student Volunteer Movement or SVM was the name of one of history’s most impactful Christian missionary movements to ever take place, and it originated in collegiate America (Ahrend, 2010). More missionaries were sent out in the first year of the Student Volunteer Movement than had been sent from the United States in the previous century. From 1890 to 1930 the SVM was comprised of 100,000 volunteers who committed to give their lives to the employment of Christian missions. Of those, 20,000 actually left America to live in other countries while 80,000 stayed behind in America. Those who stayed behind formed the Laymen's Missionary Movement to financially support the goers (Ahrend, 2010). During these forty years, this mobilization effort was able to recruit one out of every thirty-seven university students in the United States (Ahrend, 2010). Undoubtedly, there are important implications for understanding the Student Volunteer Movement if you are affiliated with a Christian campus ministry. However, if the Student Volunteer Movement were seen as only religious individuals, then one would have misunderstood the developmental excellence of the SVM. The lessons learned from the Student Volunteer Movement, transcend religious boundaries. Examining the Student Volunteer Movement helps student development educators create new ways to support students as they discover their calling. Additionally, it has implications for how faculty and professionals advise students who have calling. This paper provides an example of the relationship between student affairs professionals and spiritual development among students. This comprehensive analysis of the Student Volunteer Movement informs student affairs professionals how best to support a student’s holistic development.
Keywords: Calling; Meaning; Purpose; Spirituality; Service; Higher Education (0745)